2014
DOI: 10.1016/j.bmc.2013.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis/biological evaluation of hydroxamic acids and their prodrugs as inhibitors for Botulinum neurotoxin A light chain

Abstract: Botulinum neurotoxin A (BoNT/A) is the most potent toxin known. Unfortunately, it is also a potential bioweapon in terrorism, which is without an approved therapeutic treatment once cellular intoxication takes place. Previously, we reported how hydroxamic acid prodrug carbamates increased cellular uptake, which translated to successful inhibition of this neurotoxin. Building upon this research, we detail BoNT/A protease molecular modeling studies accompanied by the construction of small library of hydroxamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…To achieve that, we masked the hydroxamic acid functionality in 23a and 44b by synthesizing the corresponding benzyl and para-acetoxy-benzyl ester prodrugs of hydroxamic acids 59a,b and 60b (Figure 12) as prodrugs. Masking hydroxamic acids was recently reported as an approach to overcome problems like fast elimination, decreased cellular uptake and poor tissue penetration caused by the highly polar hydroxamic acid group [85][86][87][88][89][90]. In addition, paraacetoxybenzyl-based prodrugs were shown to be completely converted to the parent hydroxamic acid in plasma [91].…”
Section: Cellular Assaymentioning
confidence: 99%
“…To achieve that, we masked the hydroxamic acid functionality in 23a and 44b by synthesizing the corresponding benzyl and para-acetoxy-benzyl ester prodrugs of hydroxamic acids 59a,b and 60b (Figure 12) as prodrugs. Masking hydroxamic acids was recently reported as an approach to overcome problems like fast elimination, decreased cellular uptake and poor tissue penetration caused by the highly polar hydroxamic acid group [85][86][87][88][89][90]. In addition, paraacetoxybenzyl-based prodrugs were shown to be completely converted to the parent hydroxamic acid in plasma [91].…”
Section: Cellular Assaymentioning
confidence: 99%
“…Although we previously obtained some success using a prodrug approach, leveraged through carbamate-protected hydroxamic acids, to counteract BoNT/A LC in the cell, we also noted that this design strategy still needed improvement. (15) As an alternative means to enhance the potency of LC inhibitors, we turned our attention to Cys165, which is embedded within the active site of the BoNT/LC (highlighted with yellow in the crystal structure, Figure 1). (16) Moreover, Dive and co-workers reported that when this Cys residue was covalently modified, catalysis was stopped and the enzyme was inactivated.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive efforts over the last 2 decades have produced several in vitro and in vivo inhibitors of BoNT/A LC translocation and enzyme activity . The most potent class of BoNT/A inhibitors remains zinc-chelating molecules, particularly those inclusive of a hydroxamic acid pharmacophore. Zinc-chelating inhibitors bind competitively at the BoNT/A active site, directly preventing the association of the substrate with the enzyme catalytic site. While best-in-class reversible inhibitors have achieved sub-micromolar potency and modest protection against BoNT/A challenge in murine models, no drug candidate has reached clinical trials.…”
Section: Introductionmentioning
confidence: 99%